(untitled) (Novateur Publications, 2023)
Praise be to the presence of Allah swt. because it was His blessing that the author was able to complete the book entitled Reduplication of the Tontemboan language. In making this book, of course, we as writers were helped a lot by informants. Through informants, the author obtained the data needed for analysis. To obtain accurate data, the author chose informants who mastered the Tontemboan language so that all the required data could be obtained as expected. The author chose the Tontemboan language to see its word repetition system because the Tontemboan language has many unique features. Therefore, the author feels very interested in discussing the Tontemboan language repetition system with the hope that the presence of this book will provide scientific insight, especially in the field of language, to its readers. In the preparation of this book, of course many parties helped until it was finished. Therefore, the author would like to thank him for his participation in the preparation of this book. Our hope, as authors, is that the presence of this book will be useful for its readers.